Legal Protection for Women Drivers in the Gig Economy: Evidence from Tulungagung, East Java - Zulfiyan, Ahmad (Brawijaya Law Journal, 2020)
In patriarchal society, women tend to be vulnerable. This is caused by the existence of a hierarchical view that considers women lower position than men, even at work. This study aims to find out how the legal protection for Grab women drivers in the gig economy. The method used in this study is empirical-qualitative with a feminist approach. Data were collected through in-depth interview, literature study, and the internet. The data in this study were analyzed using the Miles and Huberman model which includes data reduction, display, and conclusion drawing. The results of this study showed that, in the gig economy, the relationship between Grab as an online transportation service provider and the drivers that they call 'mitra' cannot be categorized as an employment relationship. The implication is that the rights stated in Act Number 13 of 2003 concerning Labor cannot be obtained by drivers. In the context of women drivers, they face various legal protection constraints such as limited job security, double burden, gender stereotypes, and sexual harassment.